The New Challenges to the Equilibrium within the “China – India – Pakistan” Triangle: Political and Economic Aspects - Levitskaya, Yevgeniya (Historia i Polityka, 2017)
The economic and political aspect of the equilibrium-saving within the triangle “Delhi–Beijing–Islamabad” is the principle topic of the article. The research is based on the system methodology, thus China, India and Pakistan are presented here as the elements of the international relations subregional system. The inter-elements’ relationships are developing in the vital connection with the algorithms of the functioning of the greater system – Asia–Pacific Region. In connection with the said, the article begins with the APR characterization, the place of Southern Asia within the APR is also initially analyzed. The bilateral China-India and Paki-China relations are observed and the conclusions are formulated. Estimating the new challenges to the global international security and taking into account the considerable role of economics in the development of the countries studied, the new threats and, on the other hand, new opportunities for the uneasy interstate relationships are considered. The policy-influencing economic projects are covered in the article; IT-collaboration, co-operation within the international organizations are also considered as the restraining factors of the “triangle’s” antagonistic relations. Nevertheless, the key issue is, whether China is able to co-operate with both rival sides, avoiding the provocations. As a result of supporting one side, e.g. Pakistan, China can make India feel uneasy, in this way refreshing the old territorial disputes between the countries. Only the wise political steps can save Beijing from the collapse in its Southern Asia policy. The economic and political tools of conducting such a wise policy towards both Delhi and Islamabad are covered in the present article.